Soft Layer Identification in Kedamaian District Using the HVSR-Derived Shear Wave Velocity Distribution - Mulyana, Galang Dwi; Antosia, Risky Martin; Nathania, Edlyn Yoadan (UIR PRESS, 2026)
The Kedamaian District in Bandar Lampung City is a densely populated urban area characterized by complex geological settings that are highly susceptible to seismic amplification and geotechnical hazards. Despite its vulnerability, high-resolution characterization of subsurface soft soil deposits in this specific district remains underexplored. The study aims to evaluate local site effects for designing seismic-resistant infrastructures and mitigating geotechnical hazards. This study attempts to locate and determine the characteristics of soft soil deposits in the Kedamaian District, Bandar Lampung City, by means of the HVSR method (Horizontal to Vertical Spectral Ratio) based on the shear wave velocity distribution result. Microtremor measurements were taken from 37 points and processed to estimate the amplification factor (A0), dominant frequency of soil deposit (f0), and seismic vulnerability index (Kg). HVSR inversion used the Particle Swarm Optimization (PSO) to propose average shear wave velocity down to 30 m depth (VS30). Analysis indicated that the amplification values range from 2.31 to 9.11, with most values falling within a moderate level, indicating a moderate local site response. Dominant frequencies range from 0.63 to 18.76 Hz, and higher f0 values are characteristic of more compact and/or complex rock formations, whilst lower f0 values correspond to thicker sediments. Values of the seismic vulnerability index range from 0.48 to 119.24 s, with most sites showing a high seismic vulnerability related to the combined effect of high amplification and low dominant frequency. The distribution suggests that the study region consists predominantly of soft soils (type E) with VS30 ranging from 80.9 to 132.6 m/s, interspersed with medium soils (type D) and less abundant hard rocks (type C). The results show that the Kedamaian is primarily covered with soft sediment formations, which have the potential to enhance strong ground motion during seismic events, as well as for a geotechnical investigation database and hazard assessment of earthquake activities and urban development within the region.